Exposure of refractory materials during high-temperature gasification of a woody biomass and peat mixture. Issue 2 (February 2018) - Carlborg, Markus; Weiland, Fredrik; Ma, Charlie; Backman, Rainer; Landälv, Ingvar; Wiinikka, Henrik
Abstract: Finding resilient refractory materials for slagging gasification systems have the potential to reduce costs and improve the overall plant availability by extending the service life. In this study, different refractory materials were evaluated under slagging gasification conditions. Refractory probes were continuously exposed for up to 27 h in an atmospheric, oxygen blown, entrained flow gasifier fired with a mixture of bark and peat powder. Slag infiltration depth and microstructure were studied using SEM EDS. Crystalline phases were identified with powder XRD. Increased levels of Al, originating from refractory materials, were seen in all slags. The fused cast materials were least affected, even though dissolution and slag penetration could still be observed. Thermodynamic equilibrium calculations were done for mixtures of refractory and slag, from which phase assemblages were predicted and viscosities for the liquid parts were estimated.